If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -11 = 3x + 4 Reorder the terms: -11 + 6x = 3x + 4 Reorder the terms: -11 + 6x = 4 + 3x Solving -11 + 6x = 4 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -11 + 6x + -3x = 4 + 3x + -3x Combine like terms: 6x + -3x = 3x -11 + 3x = 4 + 3x + -3x Combine like terms: 3x + -3x = 0 -11 + 3x = 4 + 0 -11 + 3x = 4 Add '11' to each side of the equation. -11 + 11 + 3x = 4 + 11 Combine like terms: -11 + 11 = 0 0 + 3x = 4 + 11 3x = 4 + 11 Combine like terms: 4 + 11 = 15 3x = 15 Divide each side by '3'. x = 5 Simplifying x = 5
| n(2x^2+9x-5)=1+ln(x^2+2x-15) | | (7xy)(-8x)= | | log^2(3)(9X)+log^2(3)(3x)=1 | | 2x+3+x-4=45 | | 16x-9=20x+19 | | 3(-2)=-6y+3 | | 4+65x=52x+7 | | 4654x+15=50 | | 7+3a=31 | | -6=-6y+3 | | 7n-16=100 | | log^2(9X)+log^2(3x)=1 | | r^5=0.8 | | 2x+xz+y-2yz=0 | | 1+3=x-4 | | 106+66+x=180 | | 118+66+x=180 | | 54-6x=14-10x | | 2x+12=-28-6x | | x=mk+mn | | (4x+20)+(3x+40)=180 | | solvemk+mn=xform | | -3-2(5-2x)=(2x-5) | | 3+5x=-1+x | | 6x+8=-40-2 | | (-a)-b=(-b)-a | | 7=z+9 | | 9z+1=46 | | 2ln(3-x)=1 | | -a-b=-b-a | | 11x+7x+90=x+x | | b+2a+c= |